A prospective phase III, randomized, double‐blind, placebo‐controlled study of brodalumab in patients with moderate‐to‐severe plaque psoriasis4. (23rd June 2016) - Papp, K.A.; Reich, K.; Paul, C.; Blauvelt, A.; Baran, W.; Bolduc, C.; Toth, D.; Langley, R.G.; Cather, J.; Gottlieb, A.B.; Thaçi, D.; Krueger, J.G.; et al.
Summary: Background: The interleukin‐17 cytokine family plays a central role in psoriasis pathogenesis. Objectives: To evaluate the efficacy and safety of brodalumab, a human anti‐interleukin‐17 receptor antibody, in treating patients with moderate‐to‐severe plaque psoriasis. Methods: In this phase III, double‐blind, placebo‐controlled study (NCT01708590; AMAGINE‐1), adult patients in the U.S.A., Canada and Europe were randomized to brodalumab (140 or 210 mg) or placebo every 2 weeks (Q2W), with an additional dose at week 1, for a 12‐week induction phase. At week 12, patients receiving brodalumab who achieved static Physician's Global Assessment 0 or 1 (sPGA success) were rerandomized to the placebo or induction dose. After week 16, patients with sPGA ≥ 3 were re‐treated with the induction dose. After ≥ 12 weeks of retreatment, patients with sPGA 2 for ≥ 4 weeks or sPGA ≥ 3 were rescued with brodalumab 210 mg Q2W. At week 12, patients randomized to brodalumab with sPGA ≥ 2 or placebo received brodalumab 210 mg Q2W. Coprimary end points were the percentage of patients with ≥ 75% improvement in Psoriasis Area and Severity Index score (PASI 75) and sPGA success at week 12. Results: There were 661 patients randomized: 220 placebo, 219 brodalumab 140 mg and 222 brodalumab 210 mg. At week 12, 60% (140 mg) and 83% (210 mg) vs. 3% (placebo) achieved PASI 75, and 54% (140 mg) and 76% (210 mg) vs. 1% (placebo) achieved sPGA success. The safety profile was considered acceptable. Conclusions: Brodalumab therapy resulted in significant clinical benefit and an acceptable safety profile in patients with moderate‐to‐severe plaque psoriasis. Abstract : What's already known about this topic? Anti‐interleukin (anti‐IL)‐17 receptor A and anti‐IL‐17A antibodies have been shown to be efficacious in treating patients with moderate‐to‐severe plaque psoriasis. What does this study add? This study further demonstrates that brodalumab therapy in patients with moderate‐to‐severe plaque psoriasis results in a high degree of complete skin clearance. This study also further elucidates the safety profile of brodalumab. Linked Comment: Ormerod. Br J Dermatol 2016;175 :243–244 Plain language summary available online